Estimating the tax and credit-event risk components of credit spreads - Luca Benzoni; Robert S. Goldstein (Federal Reserve Bank of Chicago, 2017)
This paper argues that tax liabilities explain a large fraction of observed short- maturity investment-grade (IG) spreads, but credit-event premia do not. First, we extend Duffie and Lando (2001) by permitting management to issue both debt and equity. Rather than defaulting, managers of IG firms who receive bad private signals conceal this information and service existing debt via new debt issuance. Consistent with empirical observation, this strategy implies that IG firms have virtually zero credit-event risk (at least until they become "fallen angels"). Second, we provide empirical evidence that short maturity IG spreads are mostly due to taxes. By properly accounting for the tax treatment of capital gains and interest income associated with bond investments, we reconcile this finding with the previous literature which argues against a significant tax component to spreads.
Keywords: 330